EFFECTS OF GELESIS200, AN ORAL SUPERABSORBENT HYDROGEL, ON POSTPRANDIAL INSULIN RESPONSE IN PEOPLE WITH PREDIABETES: AN ANALYSIS OF THE LIGHT-UP STUDY - Luzi, Livio; Greenway, Frank; Miller, Sam; Matejkova, Erika; Mclean, Barry; Zmuda, Witold; Bogdanski, Pawel; Sjödin, Anders; Butcher, Michael; Wilding, John; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE Postprandial hyperinsulinemia is associated with beta- cell dysfunction and development of type 2 diabetes. This analysis assessed the effect of Gelesis200 (GS200), an investigational oral superabsorbent hydrogel, on postprandial glucose and insulin response among people with prediabetes, in the LIGHT-UP study. METHODOLOGY The LIGHT-UP study investigated the safety and efficacy of GS200 vs. placebo over 25 weeks in 254 participants with prediabetes or type 2 diabetes and a body mass index of 27-40 kg/m². The analysis included participants with prediabetes who completed a 2-hr oral glucose tolerance test at baseline and at Week 25 (42 participants per arm). Plasma glucose and serum insulin were measured at 15–30-minute intervals. Area under the curve (AUC) was calculated using the trapezoidal method and differences were assessed using ANCOVA model with weight loss as a covariate. RESULTS Participants were 59.5% female, aged 47.1 ± 11.7 years, with a fasting glucose of 104.6±10.4 mg/dL. Baseline insulin AUC was 13,005.8 ± 6,895.2 μU/mL for GS200 and 13,233.8 ± 8,268.9 μU/mL for placebo. At week 25, insulin AUC was reduced by 17.0 ± 8.2% in GS200 and increased by 5.0 ± 8.0% in placebo arms (mean difference: -22.0 ± 10.5%, P=0.04). Participants on GS200 had a greater reduction in postprandial insulin at T60 (-35.0 ± 13.1 vs. -1.5 ± 12.8 μU/mL for placebo, P=0.05) and T120 (-30.9 ± 11.6 vs. 0.5 ± 11.4 μU/mL for placebo, P=0.04), and a greater reduction in insulin Cmax vs. placebo (mean difference: -47.3 ± 21.1 μU/mL, P=0.03). No significant differences were observed for postprandial glucose or HOMA-IR between arms. CONCLUSION Administration of GS200 in people with prediabetes significantly improved postprandial insulin secretion independent of weight loss.